1991
DOI: 10.1093/ije/20.supplement_2.s43
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric History and Related Exposures as Risk Factors for Alzheimer's Disease: A Collaborative Re-Analysis of Case-Control Studies

Abstract: Data from case-control studies of Alzheimer's disease (AD) were pooled to examine the possible roles of history of depression, anti-depressant treatment and adverse life events as risk factors. History of depression was found to be associated with AD, although the effect was confined to late onset cases. The association held for episodes of depression more than 10 years before AD onset, as well as for episodes occurring within a decade of onset. No association was found with anti-depressant treatment. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
3
9

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(131 citation statements)
references
References 0 publications
8
109
3
9
Order By: Relevance
“…Risk factors for development of dementia in population studies of elderly normal subjects may be of prognostic value in patients with mild cognitive impairment. The risk factors that derive from the literature include age, 29,30 a family history of dementia, 31 history of head injury, 32,33 depression, 34,35 as well as low pre-morbid intelligence and education. [36][37][38] Female gender has been noted to be a risk factor for dementia in a number of studies, 30,[39][40][41] although this has not been found in others.…”
Section: Clinical Risk Factors For Development Of Dementia and Admentioning
confidence: 99%
“…Risk factors for development of dementia in population studies of elderly normal subjects may be of prognostic value in patients with mild cognitive impairment. The risk factors that derive from the literature include age, 29,30 a family history of dementia, 31 history of head injury, 32,33 depression, 34,35 as well as low pre-morbid intelligence and education. [36][37][38] Female gender has been noted to be a risk factor for dementia in a number of studies, 30,[39][40][41] although this has not been found in others.…”
Section: Clinical Risk Factors For Development Of Dementia and Admentioning
confidence: 99%
“…Among the medical factors suggested to be important for Alzheimer's disease are hypothyroidism (14), past history of depression (15), immune system disorders, and infectious agents (16). There is some evidence that the consumption of nonsteroidal antiinflammatory drugs (17) and estrogen replacement therapy may be protective for Alzheimer's disease (18).…”
mentioning
confidence: 99%
“…We have previously published a review of systematic reviews on behavioral and psychological symptoms in the older population (van der Linde et al, 2012), and we identified three high-quality reviews investigating the prevalence of depression and/or BPSD in different populations (Verkaik et al, 2007;Monastero et al, 2009;Luppa et al, 2010) as well as two additional reviews on the associations of depression (Jorm et al, 1991;Christensen et al, 1997). Figure 1 shows the different populations that can be included when studying depression or BPSD with several example references.…”
Section: Depression and Other Behavioral And Psychological Symptoms Omentioning
confidence: 99%